Contribution of forest products to rural household’s income and factor determining forest income in Masha district of Sheka zone, SWEPR, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
Rural people living around forests in Ethiopia depend on income from forest product collection as one of their livelihood activities. The forests of Sheka are threatened by unsustainable use and conversion to alternative land uses. This study was conducted to identify and quantify income from major forest products collected from the Sheka forest and examine factors that determine income from forest product collection. Quantitative and qualitative data were collected from primary and secondary sources. By stratified random sampling method, three kebeles were selected from the Masha district and 156 households were randomly selected from those kebeles and interviewed with a structured questionnaire. Descriptive and inferential statistics were determined by SPSS and STATA software. Multiple linear regression models were employed to determine the relationship between socio-economic factors and forest income. The result indicates 17 major forest product were collected and contributes an average of $1553.75 or 41.17% of their total annual income and was the highest contributor to total income. Forest income varies with agro-ecology and distance from the nearby markets in the study area. Households in the study area utilize more forest products for home consumption. Incomes from forest product collection are significantly related to the level of education of the household head, family size, and distance of home from the forest and market. Households in the study area depend to a higher degree on income from forest product collection and have an implication of sustainable management of forests in the long term.Int. J. Agril. Res. Innov. Tech. 12(2): 46-52, December 2022